Advances in the mechanism of inflammasomes activation in herpes virus infection - Chen, Hourui; Jian, Zhijie; Xu, Tong; Xu, Lei; Deng, Lishuang; Shao, Lina; Zhang, Leyi; He, Li; Li, Youyou; Zhu, Ling (Frontiers in Immunology, 2024)
Herpesviruses, prevalent DNA viruses with a double-stranded structure, establish enduring infections and play a part in various diseases. Despite their deployment of multiple tactics to evade the immune system, both localized and systemic inflammatory responses are triggered by the innate immune system's recognition of them. Recent progress has offered more profound understandings of the mechanisms behind the activation of the innate immune system by herpesviruses, specifically through inflammatory signaling. This process encompasses the initiation of an intracellular nucleoprotein complex, the inflammasome associated with inflammation.Following activation, proinflammatory cytokines such as IL-1β and IL-18 are released by the inflammasome, concurrently instigating a programmed pathway for cell death. Despite the structural resemblances between herpesviruses, the distinctive methods of inflammatory activation and the ensuing outcomes in diseases linked to the virus exhibit variations.The objective of this review is to emphasize both the similarities and differences in the mechanisms of inflammatory activation among herpesviruses, elucidating their significance in diseases resulting from these viral infections. Additionally, it identifies areas requiring further research to comprehensively grasp the impact of this crucial innate immune signaling pathway on the pathogenesis of these prevalent viruses.